Women's Work, Housework and Childcare, before and during Covid-19 - Daniela Del Boca; Noemi Oggero; Paola Profeta; Maria Cristina Rossi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using new survey data collected in April 2020 from a representative sample of Italian women, we analyse jointly the effect of Covid-19 on the working arrangements, housework and childcare of couples where both partners work. ties. According to our empirical estimates, changes to the amount of housework done by women during the emergency do not seem to depend on their partners' working arrangements. With the exception of those continuing to work at their usual place of work, all of the women surveyed spend more time on housework than before. In contrast, the amount of time men devote to housework does depend on their partners' working arrangements: men whose partners continue to work at their usual workplace spend more time on housework than before. The link between time devoted to childcare and working arrangements is more symmetric, with both women and men spending less time with their children if they continue to work away from home. Similar results emerge for our sample of women not working before the emergency. Finally, analysis of work-life balance satisfaction shows that working women with children aged 0-5 are those who say they find balancing work and family more difficult during Covid-19.The work-life balance is especially difficult to achieve for those with partners who continue to work outside the home during the emergency.
Keywords: J13; J16; J21; 330; Covid-19; work arrangements; housework; childcare